Care planning a guide for nurses - Wilson, Benita; Woollands, Andrea; Barrett, David 1972- (Routledge, Taylor & Francis Group, 2019)
This clear and intuitive introduction to care planning for nurses explains the benefits of holistic, individualised care planning from a professional and clinical perspective. Using the ASPIRE model, it guides the reader step-by-step through a problem-solving approach to care, from assessing patients and identifying their needs, to planning goals and interventions, and evaluating progress. The book is structured to explain the theory of care planning in relation to a number of common nursing models and then show how the theory can best be put into practice. It draws onrecent research to show how nurses can develop individualised care plans from scratch or use and adapt a range of 'off-the-shelf' tools. It is written in a clear, succinct and down-to-earth writing style, which will put students immediately at their ease, and is rich with pedagogic features, including: 'Stop and think' boxes to check understanding; boxed 'Practice examples' to illustrate points made; 'Research summary' boxes to highlight relevant and important studies; 'What have you learnt so far?' features to recap on key points of discussion; mini care plans; regular activities to encourage the reader to apply what they have learnt to particular practice scenarios.This is a go-to text for all pre-registration nursing students taking courses on the theory and practice of effective healthcare delivery